Human Rights in a Time of Populism: Philippines under Rodrigo Duterte - Pernia, Ronald A. (Animo Repository, 2019)
Although much of the researches on populism intimately delineates its relationship with democracy, few studies have been done relating it to human rights, which is presently under siege with the rise of populist leaders and groups. This paper seeks to examine the intersectionality of populism and human rights by looking at the case of the Philippines under President Rodrigo Duterte. The “new” ideational approach of populism analyzes populist ideas as latent demand or disposition that is activated and mobilized by populist actors, and appropriating the notion of “contestation.” This paper argues that Duterte’s populist political attitude is a mere reflection of the country’s authoritarian culture and illiberal values characterized, among others, by the disregard for liberal political institutions, norms, and practices. The failure of the liberal democratic regime to sufficiently respond to basic social ills was harnessed and mobilized by Duterte, the “strongman” from Davao, into political action. In addition, Duterte’s indifference and violative treatment of human rights as a principle and a standard that needs protection transpired in a highly unequal and elitist political system. This implies that turning against this populist challenge to human rights necessitates treating populism as an ideal that is initially hidden but must be surfaced. Also, although there needs to be continual opposition and contestation, there has to be an acknowledgment of populist’s structural contexts. Future studies could venture into quantification and measurement of empirical variables to complement the prevailing methodological vista of populism research in the Philippines.